Rancang Bangun Alat Pembersih dan Pengering Gabah Berbasis Arduino Uno - Pratama, Sifa Ardika; Prasetyo, Aries Alfian; Hajah, M. Sohibul (Techno Bahari, 2023)
The planning of this grain cleaning and drying machine is one of the efforts to apply appropriate technology. To assist the community in processing crop yields with a grain drying machine that is heated using a heater using a dht22 sensor. As a temperature and humidity sensor with a control system using an arduino uno as the brain of this tool . One of the reasons is that the grain drying process takes a long time because it still depends on sunny weather and requires a relatively large area. Because of that, the idea emerged to make a Design and Development of an Arduino Uno-Based Grain Cleaning and Dryer Tool. What I want to achieve from this final project is to dry grain without waiting for sunny weather first and of course it is more efficient in terms of energy and land for farmers and the community and produces good quality rice.